Electrospun piezoelectric polymer nanofiber layers for enabling in situ measurement in high-performance composite laminates - Lotfian, Saeid; Giraudmaillet, Claire; Yoosefinejad, Ata; Thakur, Vijay Kumar; Hamed, Yazdani Nezhad (American Chemical Society, 2018)
This article highlights the effects from composite manufacturing parameters on fiber-reinforced composite laminates modified with layers of piezoelectric thermoplastic nanofibers and a conductive electrode layer. Such modifications have been used for enabling in situ deformation measurement in high-performance aerospace and renewable energy composites. Procedures for manufacturing high-performance composites are well-known and standardized. However, this does not imply that modifications via addition of functional layers (e.g., piezoelectric nanofibers) while following the same manufacturing procedures can lead to a successful multifunctional composite structure (e.g., for enabling in situ measurement). This article challenges success of internal embedment of piezoelectric nanofibers in standard manufacturing of high-performance composites via relying on composite process specifications and parameters only. It highlights that the process parameters must be revised for manufacturing of multifunctional composites. Several methods have been used to lay up and manufacture composites such as electrospinning the thermoplastic nanofibers, processing an inter digital electrode (IDE) made by conductive epoxy–graphene resin, and prepreg autoclave manufacturing aerospace grade laminates. The purpose of fabrication of IDE was to use a resin type (HexFlow RTM6) for the conductive layer similar to that used for the composite. Thereby, material mismatch is avoided and the structural integrity is sustained via mitigation of downgrading effects on the interlaminar properties. X-ray diffraction, Fourier transform infrared spectroscopy, energy dispersive X-ray spectroscopy, and scanning electron microscopy analyses have been carried out in the material characterization phase. Pulsed thermography and ultrasonic C-scanning were used for the localization of conductive resin embedded within the composite laminates. This study also provides recommendations for enabling internally embedded piezoelectricity (and thus health-monitoring capabilities) in high-performance composite laminates.
Keywords: Carbon-based materials; Composites; Crystal structure; Diffraction; Electric properties; Epoxy resins; Fibers; Fluoropolymers; Mechanical properties; Piezoelectricity and Thermoelectricity; Polymer morphology; Solid state electrochemistry; Spectra; Thermal properties